Education, income and mobility: Experimental impacts of childhood exposure to progresa after 20 years - María Caridad Araujo; Karen Macours (Inter-American Development Bank (IDB), 2021)
In 1997, the Mexican government designed the conditional cash transfer program Progresa, which became the worldwide model of a new approach to social programs, simultaneously targeting human capital accumulation and poverty reduction. A large literature has documented the short and medium-term impacts of the Mexican program and its successors in other countries. Using Progresas experimental evaluation design originally rolled out in 1997-2000, and a tracking survey conducted 20 years later, this paper studies the differential long-term impacts of exposure to Progresa. We focus on two cohorts of children: i) those that during the period of differential exposure were in-utero or in the first years of life, and ii) those who during the period of differential exposure were transitioning from primary to secondary school. Results for the early childhood cohort, 18-20-year-old at endline, shows that differential exposure to Progresa during the early years led to positive impacts on educational attainment and labor income expectations. This constitutes unique long-term evidence on the returns of an at-scale intervention on investments in human capital during the first 1000 days of life. Results for the school cohort - in their early 30s at endline - show that the short-term impacts of differential exposure to Progresa on schooling were sustained in the long-run and manifested themselves in larger labor incomes, more geographical mobility including through international migration, and later family formation.
Keywords: O15; N76; I2; J18; 330; Conditional cash transfers; Long term impacts; Schooling; Early childhooddevelopment; Human capital; Mexico